ANALISA PENGARUH TEORI GONE FRAUD TERHADAP ACADEMIC FRAUD DI UNIVERSITAS MUHAMMADIYAH SUKABUMI - Ismatullah, Ismet; Eriswanto, Erlan (Universitas Muhammadiyah Surakarta, 2016)
This study intends to find out the cause of how big the effectiveness and role GONE theory against academic fraud. In this study, involving students from Sukabumi Muhammadiyah University from all exiting Program. Research conducted included in quantitative research and processed using the statistical program. The data used in this study uses primary data from questionnaires distributed to students and than do processed and analized in order to obtain results about the object and can be deduced.The results showed that of the four hypotheses proposed are two hypotheses were accepted and two rejected. Greed and Need which are internal factors inherent in a person are the root causes of academic fraud while opportunity and exposure factors which are outside factors do not have a role in the academic fraud.Â Keywords: Fraud, Academic Fraud, and GONE Theory